Detection of Laser Beam’s Center-line in 2D Images - Matiukas, V.; Miniotas, D. (Elektronika ir Elektrotechnika, 2009)
Modeling, reconstruction and visualization of 3D images is crucial in such fields as industrial engineering and manufacture, medicine, game development, etc. A physical object can be transferred to 3D virtual space by using a 3D laser scanner. Quality of the 3D model of the object scanned strongly depends on that of the laser beam’s center-line detected in the 2D image. A technique for detection of the laser beam’s center-line in a set of 2D images is presented. It uses two shifted kernels of the first-order Gaussian derivatives combined in a nonlinear way. Filtering is performed in a number of directions to select the one with the maximal response. The laser beam’s center-line is identified by the local maxima in the filtered image through evaluation of its first- and second-order derivatives. The technique was tested on images with a laser trace left on the object scanned. Ill. 7, bibl. 9 (in English; summaries in English, Russian and Lithuanian).